2005
DOI: 10.1080/03008200590954104
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Chondrocytic Properties of Fat-Derived Mesenchymal Cells in Co-Cultures with Nucleus Pulposus

Abstract: Human subcutaneous fat-derived mesenchymal cells recently have been shown to have the potential to differentiate in vitro into a variety of cell types, including adipocytes, osteoblasts, chondrocytes, and myoblasts. This effect suggests that fat tissue may serve as an abundant and easily acquired source of multipotent cells for tissue engineering. The multipotential characteristics of fat-derived mesenchymal cells from the inguinial fat pad of rabbit have not been clearly defined. In this study we have isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 22 publications
1
37
0
2
Order By: Relevance
“…Plusieurs études précliniques ont permis de démontrer la capacité de cellules « régénératrices » (cellules du NP, cellules adultes, CSM non différenciées) à synthétiser une MEC cartilagineuse en l'absence de matériau [13,27,28]. Parfois imparfaites, notamment par l'absence d'uniformité entre les matériels et les méthodes, ces études précliniques ont malgré tout permis d'envisager la mise en oeuvre d'études cliniques.…”
Section: Thérapie Cellulaire : Résultats Cliniques Actuelsunclassified
“…Plusieurs études précliniques ont permis de démontrer la capacité de cellules « régénératrices » (cellules du NP, cellules adultes, CSM non différenciées) à synthétiser une MEC cartilagineuse en l'absence de matériau [13,27,28]. Parfois imparfaites, notamment par l'absence d'uniformité entre les matériels et les méthodes, ces études précliniques ont malgré tout permis d'envisager la mise en oeuvre d'études cliniques.…”
Section: Thérapie Cellulaire : Résultats Cliniques Actuelsunclassified
“…ADSCs regenerative therapy has also been implied for the treatment of IVD diseases (O'Halloran and Pandit 2007;Gaetani et al 2008;Helder et al 2007;Li et al 2005;Richardson et al 2006): in fact, chondrocytes could be retrieved, expanded in a 3D in vitro system consisting of alginate capsules, and finally re-implanted through a mini-invasive technique. Moreover it is now possible to regenerate or replace damaged IVDs through the implants of biodegradable scaffolds seeded with autologous ADSCs previously induced to differentiate to the chondrogenic phenotype (Helder et al 2007).…”
Section: Adipose Stromal Vascular Fraction Encapsulation For Cartilagmentioning
confidence: 99%
“…Moreover, in rabbits, the adipose tissue-derived cells co-cultured with Nucleus Polposus (NP) cells showed a significant increase in the expression of type II collagen and aggrecan genes, suggesting that ADSCs might respond to mediators contained in the IVD (Li et al 2005). The barium alginate encapsulation technique applied by Gaetani et al (2008) showed that ADSCs improve the quality of in vitro reconstructed NP tissue for the regeneration of the human degenerated IVD.…”
Section: Adipose Stromal Vascular Fraction Encapsulation For Cartilagmentioning
confidence: 99%
“…After the tissue was homogenized with a rotor-stator homogenizer, total RNA was extracted and purified using a RNeasy kit (Qiagen, Chatsworth, CA); purified RNA was subjected to real-time PCR (RT-PCR) analysis according to our published protocol [22]. The sequence of primers were as follows: for type I collagen (D49399): 5 0 -CGGTGGTTACGACTTTGGTT-3 0 , 3 0 -TCAGAGTGG-CATCGACTTCA-5 0 ; for type II collagen gene (D83228): 5 0 -AACA-CTGCCAACGTCCAGAT-3 0 , 3 0 -CTGCAGCACGGTATAGGTGA-5 0 ; for aggrecan gene (L38480): 5 0 -GAGGTCGTGGTGAAAGGTGT-3 0 , 3 0 -GTGTGGATGGGGTACCTGAC-5 0 .…”
Section: Gene Expression Measured By Real-time Pcrmentioning
confidence: 99%